The Effect of Income Intention on Financial Well-Being: Household Behavior as a Mediating Variable : (Study on Women MSME Actors in Bantul Regency, Yogyakarta) - Bangun Putra Prasetya; Nany Noor Kurniyati; Raden Teja Yokanan (Digital Innovation : International Journal of Management, 2025)
Currently, people are beginning to realize that housewives actually have a role in moving the wheels of the economy and are able to achieve financial prosperity. This study uses an explanatory approach. The population in this study is female MSME actors in Bantul Regency under the guidance of related agencies. The sample in this study is 99 samples. Hypothesis testing is carried out in two stages. The first stage is testing the instrument by testing its validity and reliability. The next stage is hypothesis testing. then Mediation Test. The analysis tool using Smart PLS. shows that Income intention plays a role in influencing Financial Well-Being with a P-Value of 0.002. In addition, Income intention affects Household Behavior with a P-Value of 0.001. Household Behavior has an effect on Financial Well-Being with a P-Value of 0.000. and the mediation test showed that household behavior was able to mediate the relationship between the ability of Income intention in achieving Financial Well-Being. In addition, if a person's Income intention is balanced with the ability to control household behavior in controlling finances and saving, it will have a good impact on Financial Well-Being.